2011
DOI: 10.1161/hypertensionaha.110.162719
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate-Induced Inflammation Involves Receptor Tyrosine Kinase Transactivation in Vascular Cells

Abstract: Abstract-Sphingosine-1-phosphate (S1P), a multifunctional phospholipid, regulates vascular cell function. Whether S1P influences vascular inflammatory responses, particularly in hypertension, is unclear. We tested the hypothesis that S1P is a proinflammatory mediator signaling through receptor tyrosine kinase transactivation and that responses are amplified in vascular smooth muscle cells from stroke-prone spontaneously hypertensive rats (SHRSPs), a model in which we demonstrated Edg1 (S1P1 receptor) to be a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 48 publications
(21 reference statements)
1
23
0
Order By: Relevance
“…7 In this study, we found that both SS plasma and S1P directly enhanced monocyte-endothelial cell adhesion ( Figure 5A-B). Although S1P has been shown to alter monocyte morphology and motility through the activation of r-kinase 46 and receptor tyrosine kinases, 47 more comprehensive studies need to be performed to elucidate the receptor-specific signaling mechanism behind S1P-mediated monocyte adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…7 In this study, we found that both SS plasma and S1P directly enhanced monocyte-endothelial cell adhesion ( Figure 5A-B). Although S1P has been shown to alter monocyte morphology and motility through the activation of r-kinase 46 and receptor tyrosine kinases, 47 more comprehensive studies need to be performed to elucidate the receptor-specific signaling mechanism behind S1P-mediated monocyte adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…S1P also activated eNOS leading to NO production that acted to inhibit TNFα-stimulated adhesion molecule expression [34], suggesting that the role of S1P in vascular inflammation may depend on the level of eNOS activity and endothelial cell function. Indeed, in vascular smooth muscle cells S1P activates p38MAPK and increases VCAM-1 expression, an effect greater in cells from hypertensive than normotensive animals [23]. This raises the possibility that ET-1 activation of p38MAPK and N-SMase may lead to S1P production and adhesion molecule expression in vascular tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Pathologically, p38MAPKs are implicated in cancer, cardiac, neurodegenerative and inflammatory diseases [21]. Increased p38MAPK activity is reported in arteries and vascular smooth muscle cells from animal models of cardiovascular disease [22,23] and activation of p38MAPKs in vascular tissue induces production of inflammatory markers in the arterial wall [24]. Although ET-1 is a potent activator of p38MAPK in vascular cells and tissues [25], the involvement of this pathway in pro-inflammatory effects is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Different from other immune modulators, S1P is a lipid with significant pleiotropic activities, which can interact with five different receptors to activate signaling pathways and also act as an intracellular second messenger (Spiegel and Milstien, 2011). Yet, as the impaired phosphorylation of its receptor 1 (S1P 1 ) boosts Th17 polarization, exacerbating autoimmune neuroinflammation (Garris et al, 2013), and S1P also mediates vascular inflammation (Yogi et al, 2011), there is a need for studies using the relevant animals models, i.e., NHP, before testing it in humans.…”
Section: Phosphorylcholine Based Th2 Adjuvantsmentioning
confidence: 99%